Prevalence and social correlates of sexual intercourse among schoolgoing adolescents in Namibia - Kazhila Croffat Chinsembu; Seter Siziya; Adamson S Muula; Emmanuel Rudatsikira (Taylor & Francis Group, 2008)
Adolescent sexuality is an important public health issue, as it affects risk to contract HIV and other sexually transmitted infections. The assessment of prevalence of sexual intercourse among adolescents is of public health significance, as it may guide policies and programmes aimed at reducing the transmission of sexually transmitted infections among this age group. This cross-sectional study using standardised methodology was conducted to assess the prevalence and correlates of sexual intercourse among Namibian schoolgoing adolescents in 2004. Overall the prevalence of sexual intercourse was 33.2% (44.0% males and 24.8% females). Variables positively associated with the outcome in multivariate analysis were male gender (OR=2.39; 95% CI (1.81, 3.17)), cigarette smoking (OR=1.67; 95% CI (1.07, 2.63)), alcohol drinking (OR=1.63; 95% CI (1.18, 2.26)), and drug use (OR=9.82; 95% CI (6.28, 15.36). Parental supervision was negatively associated with sexual intercourse in the last 12 months (OR=0.73; 95% CI (0.56, 0.94)). Efforts to control unhealthy lifestyles (smoking, alcohol and illicit drug use) may impact on adolescents' sexual activity.